The utilization of appropriate technology in the form of breastshot to support agrotourism in Sawah Pelangi Pelawan - Al Afifah; Desgita Alvi Fitri; Marina Marina; Muallimin Muallimin; Nur Azizah Sirait; Renaldo Prayoga; Rini Septiani; St Ainun Abdullah; Viki Nadi; Zikri Alamsyah; Nurjannah Nurjannah (Community Empowerment, 2023)
Water is the primary necessity for rice fields, and if not managed effectively, it can pose challenges. Rice fields in Namang village serve as both a source of sustenance and a cornerstone of the community's economy. The objective of this community service program is to promote the use of appropriate technology in the form of a breastshot wheel to address water supply shortages. Additionally, it aims to bolster the growth of agrotourism in Sawah Pelangi Pelawan. The program unfolds in various stages, program planning, public awareness initiatives, tool assembly and tool testing. The evaluation findings underscore the high satisfaction of Namang village residents with the adoption of this appropriate technology, as the advantages of the breastshot wheel directly meet the water requirements of rice fields and enhance agrotourism attractions.